Nexo agua-energía-alimentos: rentabilidad y riesgo en portafolio de inversión escenario postpandemia - CARRILLO BARBOSA, Yazmid Adriana (2024)
The primary objective of this study was to evaluate the profitability and risks associated with the Water-Energy-Food (WEF) nexus portfolio in the post-pandemic scenario. For this purpose, a quantitative and cross-sectional methodology was employed, based on the analysis of a variety of commodities representing these sectors, such as California water bonds, Brent crude oil, natural gas, corn, soy, and coffee. The analysis was conducted using a Python-developed algorithm, focused on assessing the portfolio's profitability, risk, and Markowitz's Efficient Frontier. The results indicate that, although there are profitability opportunities in the WEF nexus portfolio, significant risks are also present for achieving such profitability. A key finding of the study is that, despite the increasing demand for efficient and sustainable resources, investment in these sectors requires strategic and considered management. The need for careful portfolio selection and diversification is suggested, aligning investments with sustainability principles to ensure their long-term viability. The study concludes by highlighting the importance of developing more robust predictive models and advocates for future research for a more comprehensive analysis of the dynamics between water, energy, and food and their impact on financial markets.